2018
DOI: 10.1097/shk.0000000000000989
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicle Subsets in Sepsis Due to Community Acquired Pneumonia Compared to Faecal Peritonitis

Abstract: Plasma MV profiles vary according to the source of infection. A2MG MV are associated with survival in CAP but not FP. We propose specific MV subsets as novel biomarkers in sepsis and potential effector for some of the actions of experimental therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…Second, the suppression of TNF release by neutrophil-MDM co-culture supernatants, which is abolished by ultracentrifugation, indicates a requirement for complexes of mediators and/or released extracellular vesicles. Microvesicles released from viable neutrophils exert immunosuppressive activity in vitro 27 29 and in vivo 9 when highly concentrated and display several phenotypes 30 . However, our observations suggest that two-way communication between the macrophage and neutrophil is required to induce release of the required mediators.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the suppression of TNF release by neutrophil-MDM co-culture supernatants, which is abolished by ultracentrifugation, indicates a requirement for complexes of mediators and/or released extracellular vesicles. Microvesicles released from viable neutrophils exert immunosuppressive activity in vitro 27 29 and in vivo 9 when highly concentrated and display several phenotypes 30 . However, our observations suggest that two-way communication between the macrophage and neutrophil is required to induce release of the required mediators.…”
Section: Discussionmentioning
confidence: 99%
“…The “sepsis” diagnosis encompasses patients with a multitude of scenarios by which the microbial invasion develop. To our knowledge, only one recent study compared the role of EVs among subsets of septic patients based on the site of infection 16 .…”
Section: Heterogeneity Versus Standardization: Critical Assessment Ofmentioning
confidence: 99%
“…In at least 14 studies, the septic patients were in the state of shock. It is unknown whether re-analysis of sepsis studies using the new Sepsis-3 definitions for enrollment (and thus redistributing groups) would change their conclusions; new studies selecting patients based on the new Sepsis-3 have been only recently emerging 16 . Interestingly, redistribution of patients according to the Sepsis-3 definition did not affect conclusions drawn in the recent study by Matsumoto et al 19 .…”
Section: Heterogeneity Versus Standardization: Critical Assessment Ofmentioning
confidence: 99%
“…Elevated plasma extracellular vesicle concentrations were associated with a lower risk of developing ARDS; this association was seen most strongly in patients admitted to ICU with sepsis. Another group of investigators [23] found that a subset of circulating leukocyte extracellular vesicles expressing α2-macroglobulin (A2MG) were associated with survival in ICU patients with sepsis secondary to pneumonia, but not in patients with sepsis secondary to fecal peritonitis. A2MG-EV treatment in vitro reduced endothelial cell permeability and increased bacterial phagocytosis by neutrophils.…”
Section: Potential Endogenous Protective Effects Of Extracellular Vesmentioning
confidence: 99%
“…Several studies that have investigated the role of extracellular vesicles in acute lung injury and ARDS have been done in animal and in vitro models, although one recent study was done in the ex vivo perfused human lung [12], and there are a few clinical studies as well [13,18,[21][22][23]. Future studies will need to characterize BALF and circulating extracellular vesicles from ARDS patients with regard to the cell of origin, cargo assessment (RNA, protein, organelle content), and their biological effect on human cells and human tissues.…”
Section: Future Directionsmentioning
confidence: 99%